Invasive Pulmonary Aspergillosis and Nocardia Pneumonia in a Pediatric Patient With Chronic Lung Disease: A Case Report - Ahmed H. Ali; Mahmoud Kamal; Mohammed E. Elyan (Case Reports in Pediatrics)
This case illustrates the susceptibility of pediatric patients with chronic lung disease, here, a 3-year-old male with structural airway injury and impaired mucociliary clearance from recurrent aspiration (due to Chiari II malformation and spinal dysgenesis), to life-threatening polymicrobial co-infections, even without classic immunodeficiency. The child was admitted with acute respiratory failure and sepsis; imaging demonstrated necrotizing pneumonia and pneumatoceles; bronchoalveolar lavage confirmed ∗Aspergillus∗ galactomannan positivity and ∗Nocardia∗ species, warranting broad antimicrobial therapy and mechanical ventilation. Diagnosis of invasive aspergillosis and treatment initiation were delayed; despite therapy, he developed multiorgan failure and died. This highlights how chronic lung disease predisposes children to catastrophic fungal–bacterial synergies and reinforces the value of early bronchoscopy for targeted treatment. Advanced disease with structural damage portends poor outcomes, underscoring the need for enhanced surveillance in this high-risk cohort.